Neurological Impress Method (NIM) Towards Student’s Reading Ability - Indah Tri Lestari (Channing : Journal of English Language Education and Literature, 2018)
This study aimed at finding out whether or not there are any significant differences between the students who are taught by using neurological impress method and the students who are taught by using a conventional method in reading ability. The population of this study was 63 students of SMK Nurul Huda Sukaraja. From the population, there were 22 students taken as a sample of experimental class and 21 students were as control class. The sample was taken using purposive sampling. In carrying out the study, the writer used a quasi-experimental design. Finally, the data were analyzed by using the independent t-test formula. And based on the result of findings, it was found that the mean of posttest score in the experimental class was 6.83 and the control class was 5.08. Beside that, the t-obtained was 6.25 and the t-table with df 41 (43-2) with 0.05 significant level was 2.02. therefore, the study concludes that the alternative hypothesis (Ha) was accepted because the t-obtained was lowest than the t-table (6.25 > 2.02). It also meant that there were any significant differences between students who are taught by using Neurological Impress Method (NIM) and who are taught by using Conventional Method.